DIMENSION OF SERVICE QUALITY (RATER) ON CONSUMER SATISFACTION - Ahmad Farhani (stiatabalong.ac.id, 2023)
This study aims to examine the Dimensions of Service Quality (RATER) on Consumer Satisfaction in the building shop owned by Mr. H. Ijul in Tabalong Regency. The tight competition in the world of trade requires business actors to have a competitive and sustainable advantage, business actors must have the right marketing strategy, one of which is paying attention to factors that can provide maximum satisfaction to their consumers. This study uses 5 exogenous variables, namely, reliability, assurance, tangible, empathy responsiveness, while the endogenous variable is customer satisfaction. Sampling was done by purposive sampling totaling 166 respondents. The data analysis technique used Variance Based SEM (PLS-SEM) with SmartPLS 3.29 software. The results showed that the responsiveness, reliability, assurance and tangible variables had a positive and significant effect on consumer satisfaction, while the empathy variable had a negative and insignificant effect on consumer satisfaction. The implication must be good management in changing its strategy by maximizing indicators on reliability, assurance, tangible empathy. Responsiveness provided by the store to consumers Keywords: Dimensions of Service Quality; RATER ; Store building ; SEM ; SmartPLS ; Consumer Satisfaction